APLIKASI SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SISWA BERMASALAH MENGGUNAKAN METODE SAW PADA SEKOLAH SMP SWASTA MULIA PRATAMA MEDAN - Hengki Tamando Sihotang; Maria Santauli Siboro (STMIK Pelita NUsantara, 2016)
ABSTRACT The process of finding and ranking troubled students is one important part of school activities, counseling has an important role in guiding the student face a varietyof problems, so that education can produce graduates who have a strong personality. The quantity of student data that must be processed to determine the priority of student who are entitled to guidance counseling should have in Decision Making Process. The concept of decision support program is growing very rapidly. Many methods are used to assist in the decision making process. One way that can be used to solve problems of Multi Attributes Decision Making (MADM) with the SAW (Simple Additive Weighting) method. Because the method is simple concept, easily understood, computationally efficient and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. In this case method aims to help everyone in making decisions based on the best value alternatif. With the rapid advancement of technology today, bring an idea or notion of the writer to attempt to computerize the system of decision-making problems in junior high students Private Medan Mulia Pratama. The author tries to build an application that will help to facilitate the students' decision-making problem which includes data input rating of students and students looking for the most problematic, with the aim of facilitating the processing of data is more optimal and effective. The system will be made is